SCIENTIFIC AND TECHNICAL SOLUTIONS FOR MECHANIZED HARVESTING OF POTATOES IN THE CONDITIONS OF UZBEKISTAN - Norchaev Rustam; Norchaev Zhaloliddin Rustamovich; Rustamova Nigora Rustamovna (Galaxy International Interdisciplinary Research Journal, 2021)
In the conditions of Uzbekistan, when harvesting early potatoes in the summer, the soil moisture is low. Therefore, in the process of digging, the soil of the tuberous layer crumbles poorly with the formation of large lumps, which makes it difficult to separate them from the tubers on a roar and an elevator. This leads to increased loss and damage of potato tubers.Therefore, research is required to develop a more efficient method of harvesting tubers,providing the required quality of work with less energy consumption and greater productivity. The developed design parameters of potato diggers are described.